2004
DOI: 10.1007/s00417-004-0874-2
|View full text |Cite
|
Sign up to set email alerts
|

Induction of IL-8, MCP-1, and bFGF by TNF-α in retinal glial cells: implications for retinal neovascularization during post-ischemic inflammation

Abstract: The results indicate that TNF-alpha is produced by activated macrophages/microglia and may participate in retinal neovascularization during post-ischemic inflammation through the induction of potent angiogenic factors in an autocrine or paracrine manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
79
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(85 citation statements)
references
References 18 publications
5
79
0
1
Order By: Relevance
“…TNF-is an angiogenic molecule produced by hypoxic monocytes/macrophages (Yun, et al, 1997) and is a likely mediator of retinal neovascularization/revascularization. It has been reported that TNF-level is higher in patients with PDR (Limb, et al, 2001), and we have detected this molecule in the macrophages/BM-MLCs in murine OIR (Yoshida, et al, 2004). Moreover, we have demonstrated that TNF-up-reguletes the production of IL-8, VEGF, bFGF, or MCP-1 in retinal vascular cells and/or glial cells adjacent to microvessels triggering neovascularization/revascularization in an autocrine or paracrine manner (Yoshida, et al, 2004;Yoshida, et al, 1997).…”
supporting
confidence: 69%
See 1 more Smart Citation
“…TNF-is an angiogenic molecule produced by hypoxic monocytes/macrophages (Yun, et al, 1997) and is a likely mediator of retinal neovascularization/revascularization. It has been reported that TNF-level is higher in patients with PDR (Limb, et al, 2001), and we have detected this molecule in the macrophages/BM-MLCs in murine OIR (Yoshida, et al, 2004). Moreover, we have demonstrated that TNF-up-reguletes the production of IL-8, VEGF, bFGF, or MCP-1 in retinal vascular cells and/or glial cells adjacent to microvessels triggering neovascularization/revascularization in an autocrine or paracrine manner (Yoshida, et al, 2004;Yoshida, et al, 1997).…”
supporting
confidence: 69%
“…It has been reported that TNF-level is higher in patients with PDR (Limb, et al, 2001), and we have detected this molecule in the macrophages/BM-MLCs in murine OIR (Yoshida, et al, 2004). Moreover, we have demonstrated that TNF-up-reguletes the production of IL-8, VEGF, bFGF, or MCP-1 in retinal vascular cells and/or glial cells adjacent to microvessels triggering neovascularization/revascularization in an autocrine or paracrine manner (Yoshida, et al, 2004;Yoshida, et al, 1997). These processes are likely to be important in promoting macrophages/ BM-MLCs-related retinal neovascularization/revascularization in hypoxic retinas.…”
supporting
confidence: 69%
“…The VEGF through VEGFR2 induces endothelial cell proliferation and increases cerebral vascular permeability, whereas interaction of Ang-1 with its receptor, Tie2, protects against VEGFinduced brain-blood barrier leakage (Thurston et al, 1999(Thurston et al, , 2000Wu et al, 2003). The TNF/TNFR1 can directly act on endothelial cells to induce angiogenesis through activation of the VEGF pathway (Sugano et al, 2004;Yoshida et al, 2004). Our data showed that both rhTNF and rhEPO, but not rhTNF or rhEPO alone, at the concentration used in this study upregulated VEGF/VEGFR2 and Ang1/ Tie2, which was mediated by EPOR.…”
Section: Figurementioning
confidence: 99%
“…Moreover, previous reports have shown that retinal ischaemia stimulates IL-8 and MCP-1 production, and both chemokines are involved in retinal neovascularization. [31][32][33][34] Although ischaemia as seen using FFA was one of the exclusion criteria, we cannot absolutely exclude that this was present in our patients. So retinal ischaemia may have also contributed to hyperproduction of IL-8 and MCP-1.…”
Section: Il-8 and Mcp-1 In Brvo Macular Oedemamentioning
confidence: 99%